Plant-Derived Compounds as a Tool for the Control of Gastrointestinal Nematodes: Modulation of Abamectin Pharmacological Action by Carvone - Miró, M. V.; Luque, S.; Cardozo, P.; Lloberas, M.; Sousa, D. M.; Soares, A. M. S.; Costa-Junior, L. M.; Virkel, G. L.; Lifschitz, Adrian L. (Frontiers in Veterinary Science, 2020)
The combination of synthetic anthelmintics with bioactive phytochemicals may be a pharmacological tool for improving the nematode control in livestock. Carvone (R-CNE) have shown in vitro activity against gastrointestinal nematodes, but the anthelmintic effect of bioactive phytochemicals alone or combined with synthetic drugs has been little explored in vivo. Thus, this work assessed in vitro and in vivo the pharmacological interaction of abamectin (ABM) and R-CNE. The efficacy of this combination was evaluated in lambs naturally infected with resistant gastrointestinal nematodes. Additionally, the ligand and molecular docking of both molecules to P-gp was studied in silico. The presence of R-CNE increased significantly (p<0.05) Rho123 and ABM accumulation in the intestinal explants. After 60 min incubation, the concentration of Rho123 was 67 ± 21 % higher (p<0.01) when it was incubated with R-CNE compared with that measured when the substrate was incubated alone. In the case of ABM the significant increment in the intestinal concentrations was observed at 15 and 30 min after incubation with R-CNE. In the in vivo assay, no undesirable effects were observed after the oral administration of R-CNE. The coadministration of the natural compound prolonged ABM absorption in lambs. ABM T½ absorption was 1.57-fold longer (p<0.05) in the co-administered group. Concentrations of R-CNE between 420 and 2593 ng/mL were detected in the bloodstream between 1 and 48 h post-treatment. The in vivo efficacy of ABM against gastrointestinal nematodes increased from 94.9 % to 99.8 % in the presence of R-CNE, with the lower confidence interval limit above 90 %. In vitro / in vivo pharmaco-parasitological studies are relevant for the knowledge of the interactions and the efficacy of bioactive natural products combined with synthetic anthelmintics. While ADMET predictions and molecular docking study showed the ABM interaction with P-gp, R-CNE would not appear to modulate this efflux protein. Therefore, the pharmacokinetic-pharmacodynamic effect of R-CNE on ABM should be explained by its effect on membrane permeability. The development of pharmacology-based information is critical to design successful strategies for the future of parasite control.